Software modeling and design process - Dwivedi S. (My University, 2025)
Modeling is the designing of software applications before coding according to the object-oriented groups where under the model-based software design and development, software modeling and design are used as an important and mandatory part of the software development process. Software models are methods of expressing a software design. Basically, some sort of abstract language or pictures are used to express the software design under modeling. For object-oriented software, an object modeling language such as UML and many more are used to develop and express the software design. Also, the design model is based on the analysis and architectural essentials of the system. It denotes the application components and determines their appropriate placement and use within the overall architecture. © 2023, IGI Global. All rights reserved.